Hybrid White Light Emitting Diode Based on Silicon Nanocrystals. (8th September 2014) - Ghosh, Batu; Masuda, Yoshitake; Wakayama, Yutaka; Imanaka, Yasutaka; Inoue, Jun‐ichi; Hashi, Kenjiro; Deguchi, Kenzo; Yamada, Hideto; Sakka, Yoshio; Ohki, Shinobu; Shimizu, Tadashi; Shirahata, Naoto
<x xml:space="preserve">Abstract</x> A novel design of white light emitting diodes (WLEDs) emerges to meet the growing global demand for resource sustainability while preserving health and environment. To achieve this goal, a facile method is developed for the chemical synthesis of a luminescent silicon nanocrystal (ncSi) with a large Stokes shift between absorption and emission. The WLED is prepared by a simple spin‐coating method, and contains a hybrid‐bilayer of the ncSi and luminescent polymer in its device active region. Interestingly, a well‐controlled ultrathin ncSi layer on the polymer makes possible to recombine electrons and holes in both layers, respectively. Combining red and blue‐green lights, emitted from the ncSi and the polymer layers, respectively, produces the emission of white electroluminescence. Herein, a hybrid‐WLED with a sufficiently low turn‐on voltage (3.5 V), produced by taking advantages of the large Stokes shift inherent in ncSi, is demonstrated.